Contamination characteristics, source analysis and health risk assessment of heavy metals in the soil in Shi River Basin in China based on high density sampling - Yuqi Zhang (Elsevier, 2021)
To explore the contamination of heavy metals in the Shi River Basin soil in China, a high density sampling of surface soil was conducted. In this study, an absolute principal component scores multiple linear regression model (APCS-MLR) was used to identify the sources of heavy metals in the soil and quantify their amounts. The methods to assess the heavy metals included a fuzzy synthetic evaluation, index and health risk assessment. The results show that heavy metals are relatively rich southwest of the study area. Their levels may be affected by natural sources, such as parent materials. The pollution caused by human factors cannot be ignored, and it is primarily influenced by traffic emissions and processing sources, which contribute 62.6%, followed by agricultural sources, such as pesticides and fertilizers, that contribute 21.1%. The risk assessment indicated that the study area was slightly to moderately polluted. All heavy metals pose higher carcinogenic and other health risks to children than adults, and ingestion is the main way that these pollutants enter the body. The carcinogenic risk of children owing to Cr from natural sources merits further study, while the carcinogenic risk to adults and the non-carcinogenic risk to both adults and children are at acceptable levels. Transportation and industrial processing sources are the main cause of the non-carcinogenic risk. The results could provide reference for reducing heavy metal pollution in the soil.